Karakteristik zodia (Evodia suaveolens) asal Papua berpotensi bagi industri hulu produk pertanian - Iriani, Farida (Cassowary, 2023)
The purpose of this study was to determine the types of phytochemical compounds in the organs of the bark, leaves, roots and seeds of the zodia plant. Dried materials from zodiac plant organs (roots, bark, leaves, and seeds) were macerated with ethanol compounds for 3x24 hours, then distilled so that the ethanol compounds evaporate, then macerated again with methanol solvent to obtain a clear macerate, and ended with evaporation with a rotary vacuum device at 50oC. The results of simplisia were identified various phytochemicals contained in each organ through GCMS chromatography tool type QP-2010. Types of phytochemicals are identified and what are their concentrations, as well as how their potential for the development of agricultural products from each zodiac plant organ are the objectives of this experiment. The chromatograms identified various phytochemicals, namely, 56 types of roots, 23 types of leaves, 18 types of stem bark, and 13 types of seeds. Benzene, cyclopentane, and hexane compounds were present in all four organs tested, typical compounds in roots (nonadecane), stem bark (aristolone), leaves (evodiamine and selin), and seeds (longiverbenone). Some zodia plant phytochemicals act as antimicrobials, antifungals, and antibacterials, so they have the potential to be utilized as industrial materials for upstream agricultural products.